New insights into diabetes-induced cardiac pathology - Weeks, K.L.; Bernardo, B.C.; Bell, J.R.; Delbridge, L.M.D.; Mellor, K.M. (Journal of molecular and cellular cardiology, 2025)
Individuals with diabetes have an elevated risk of heart disease, and there is a significant clinical need for evidence-based treatments. Heart disease in diabetes manifests as a distinct cardiopathology, with cardiac structural and functional remodeling underlying increased susceptibility to cardiac dysfunction and arrhythmias. An understanding of the mechanisms associated with cardiac vulnerability in diabetes is incomplete, but recent studies have advanced new insights into the roles of metabolic disturbances, gene dysregulation and epicardial adipose influence. This perspective article highlights these three promising new developments in proposed mechanisms, and discusses exciting advances in cardiac-targeting for potential treatment of diabetic heart disease. •Metabolic disturbances in the diabetic heart are complex & require further investigation.•Non-coding RNAs regulate numerous processes in the diabetic heart & are potential drug targets.•Epicardial adipose is emerging as a key contributor to diabetic & other cardiac pathologies.•Novel treatment modalities hold promise for diabetic heart disease.